Impact of 11q Loss of Heterozygosity Status on the Response of High-Risk Neuroblastoma With MYCN Amplification to Neoadjuvant Chemotherapy - Lu, Xian-Ying; Qu, Li-Jun; Duan, Xian-Lun; Zuo, Wei; Sai, Kai; Rui, Gang; Gong, Xian-Feng; Ding, Yi-bo; Gao, Qun (Frontiers in Pediatrics, 2022)
Purpose: The aim of this study was to investigate whether 11q loss of heterozygosity (LOH) aberration would impact the response of the primary tumour to neoadjuvant chemotherapy or to the degree of surgical resection in neuroblastoma (NB) patients with MYCN amplification. Methods: The clinical data of 42 NB patients with MYCN amplification who were newly diagnosed and received treatments at our hospital from 2011 to 2020 were retrospectively analysed. According to the results of the segmental chromosome aberration analysis, the patients enrolled were assigned to an 11qLOH positive group and an 11qLOH negative group. Results: There was no significant difference in the mean number of chemotherapy courses completed before surgery between the 11qLOH positive and 11qLOH negative groups (p = 0.242). Each of the 42 patients had metaiodobenzylguanidine (MIBG) scans both before and after neoadjuvant chemotherapy. The percentage of patients who had a clinical MIBG change in the 11qLOH positive group was lower than the percentage in the 11qLOH negative group (27.27% vs. 66.67%, p = 0.030). The 11qLOH negative group seemed to have a higher rate of surgical resection (greater than or equal to 90%); however, the difference between the two groups was not statistically significant (p = 0.088). Furthermore, the 11qLOH negative group did not show significantly superior event-free survival and overall survival rates compared with the 11qLOH positive group. Conclusions: This study showed that patients with NB and MYCN amplification in combination with 11qLOH might be less likely to respond to neoadjuvant chemotherapy when compared with patients with NB and MYCN amplification without 11qLOH.